ANALISIS YURIDIS TERHADAP PUTUSAN PENGADILAN TINDAK PIDANA KORUPSI NOMOR 33/PID.SUS-TPK/2025/PN PLG TENTANG PENYALAHGUNAAN WEWENANG DALAM PENERBITAN IZIN USAHA PERKEBUNAN (PENDEKATAN KASUS DAN PERUNDANG-UNDANGAN) - Alvan Rahfiansyah Lubis (PT. Hasba Edukasi Mandiri, 2025)
This research aims to analyze the legal application in the Decision of the Corruption Crime Court No. 33/Pid.Sus-TPK/2025/PN Plg, which sentenced Dr. Ridwan Mukti, former Regent of Musi Rawas, for corruption in the form of abuse of authority in granting plantation business permits to PT. Dapo Agro Makmur. This study uses a normative juridical method with case and statutory approaches. Data were obtained through literature studies by analyzing court decisions, statutory provisions, and relevant legal literature. The results show that the element of abuse of authority was proven based on formal evidence and judicial consideration. Although material state loss could not be proven, the defendant’s actions violated the principles of legality, propriety, and good governance. The court sentenced him to two years and six months imprisonment and a fine of five hundred million rupiahs as legal accountability. This research concludes that consistent legal enforcement against public officials is essential to prevent misuse of administrative authority and to uphold integrity and justice in public governance.